Islamic Economics and Sustainable Development Goals (SDGs): Bridging the Gap through Ethical Financial Practices - Hotman, Hotman (Penelitian dan Pengembangan Ilmu, 2024)
Islamic financial practices are an important research subject in the context of achieving Sustainable Development Goals (SDGs). This research investigates the contribution of Islamic financial practices to achieving the SDGs through a systematic analysis of related literature. Various Islamic financial practices, including the use of sharia financial contracts, implementation of zakat, infaq, and alms, as well as engagement in responsible social and environmental investments, are evaluated in the context of their impact on financial inclusion, economic empowerment, environmental protection, and overcoming social inequality. . The research results show that Islamic financial practices have great potential in supporting the achievement of SDGs. Policy implications and further research directions are also discussed.